Data center energy conservation study utilizing loop heat pipes as a chip-level cooling technique and its industrial application. (5th February 2023) - Xue, Zhi Hu; Ai, Bang Cheng; Qu, Wei
Highlights: The operating principle of LHP chip-level cooling approach is initiatively presented. An energy-saving theoretical model using LHPs for datacenter conservation is developed and verified. Two kinds of servers with LHP-cooled work well. Two industrial datacenters based on LHP chip-level cooling technique are practiced. The application results are in accordance with the theoretical results. Abstract: The thermal management and energy consumption for data centers became an increasing challenge due to a significant increase in their number, size and power density in modern information and digitization age. The electricity using by cooling system contributed the important fraction of energy consumption in datacenters, and it is of great significance to carry out the research of new cooling technologies to improve the cooling efficiency of datacenters. This paper initiatively presents the basic energy conservation principle of chip-level cooling technique based on the loop heat pipe (LHP) for natural cooling throughout a year. An energy-saving theoretical evaluation model based on the LHP chip-level cooling method is developed for assessing the energy utilizing efficiency and energy-saving levels in datacenters. Two kinds of real computer servers using two water-cooling LHPs with flat evaporator are introduced. The evaporator volume of a LHP is 54 × 44 × 12 mm 3 . The tests show that the servers work safely with the inlet water temperature of 40 °C and flow rate of 0.027 m 3 /h in the condenser of LHP. Lastly, the applications in two industrial data centers based on the LHP chip-level cooling technique are practiced. The annual cooling-PUE of a cloud-computing datacenter in Hohhot city is 1.053, and the annual PUE of a supercomputer-center in Beijing city is 1.15. Their operation data both show that the energy savings of the cooling system and the whole data center could be up to 81 % and 30 % respectively compared to the traditional CRAH cooling technique, which are in accordance with the predicted results of theoretical evaluation model.